A Numerical Study of the Impact of Radial Baffles in Solid Bowl Centrifuges Using Computational Fluid Dynamics. (29th July 2010) - Romaní Fernández, Xiana; Nirschl, Hermann
Abstract : Centrifugal separation equipment, such as solid bowl centrifuges, is used to carry out an effective separation of fine particles from industrial fluids. Knowledge of the streams and sedimentation behavior inside solid bowl centrifuges is necessary to determine the geometry and the process parameters that lead to an optimal performance. Regarding a given industrial centrifuge geometry, a grid was built to calculate numerically the multiphase flow of water, air, and particles with a computational fluid dynamics (CFD) software. The effect of internal radial baffles on the multiphase flow was investigated. The results show that the baffles are helpful for the acceleration of the fluid, but they disturb the axial boundary layer, making it irregular, and originate a secondary circulating flow which hinders the sedimentation of small particles.